BASIC PRINCIPLES OF A HEALTHY LIFESTYLE AMONG YOUNG PEOPLE - GULMIRA S. MALIKOVA,; LYUBOV A. REMPEL,; SAROFATKHON X. PARPIYEVA, (World Scientific Research Journal, 2025)
Abstract: A person's well-being is influenced by various indicators, including health. In order to be in good shape, both physically and psychoemotionally, you should not forget about nutrition, sleep, training and, in general, pay attention to satisfaction with your own life.